2007
DOI: 10.1093/fampra/cmm075
|View full text |Cite
|
Sign up to set email alerts
|

A new diagnostic rule for deep vein thrombosis: safety and efficiency in clinically relevant subgroups

Abstract: The rule can safely exclude DVT in primary care patients suspected of DVT, irrespective of age, gender and history of DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…As Carrier et al also found, we concluded that a low risk according to the clinical decision rule in combination with a negative D-dimer result can effectively exclude DVT in the elderly. Interestingly, in contrast to the study of Carrier et al in the elderly hospital outpatients, but in accordance with other studies [11,12], we found a higher prevalence of DVT in the older age groups: The prevalence of DVT in our study ranged from 16.7% (aged < 50 years) to 21.7% (aged ‡ 70 years; Table 1) [6]. To improve the rulesÕ efficiency in the oldest age group ( ‡ 70 years), we proposed to redefine the cut-off values of the D-dimer to 1000 ng L )1…”
supporting
confidence: 90%
See 4 more Smart Citations
“…As Carrier et al also found, we concluded that a low risk according to the clinical decision rule in combination with a negative D-dimer result can effectively exclude DVT in the elderly. Interestingly, in contrast to the study of Carrier et al in the elderly hospital outpatients, but in accordance with other studies [11,12], we found a higher prevalence of DVT in the older age groups: The prevalence of DVT in our study ranged from 16.7% (aged < 50 years) to 21.7% (aged ‡ 70 years; Table 1) [6]. To improve the rulesÕ efficiency in the oldest age group ( ‡ 70 years), we proposed to redefine the cut-off values of the D-dimer to 1000 ng L )1…”
supporting
confidence: 90%
“…In a similar study in the primary care setting, published a few months earlier, we obtained similar results and drew similar conclusions for this setting [6]. That study included 2086 consecutive primary care patients suspected of having DVT selected from 110 physicians in The Netherlands.…”
supporting
confidence: 73%
See 3 more Smart Citations